Analisis Teoritis dan Empiris Uji Craps dari Diehard Battery of Randomness Test untuk Pengujian Pembangkit Bilangan Acaksemu - Hafman, Sari Agustini; Rozi, Arif Fachru (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2013)
According to Kerchoffs (1883), the security system should only rely on cryptographic keys which is used in that system. Generally, the key sequences are generated by a Pseudo Random Number Generator (PRNG) or Random Number Generator (RNG). There are three types of randomness sequences that generated by the RNG and PRNG i.e. pseudorandom sequence, cryptographically secure pseudorandom sequences, and real random sequences. Several statistical tests, including diehard battery of tests of randomness, is used to check the type of randomness sequences that generated by PRNG or RNG. Due to its purpose, the principle on taking the testing parameters and the test statistic are associated with the validity of the conclusion produced by a statistical test, then the theoretical analysis is performed by applying a variety of statistical theory to evaluate craps test, one of the test included in the diehard battery of randomness tests. Craps test, inspired by craps game, aims to examine whether a PRNG produces an independent and identically distributed (iid) pseudorandom sequences. To demonstrate the process to produce a test statistics equation and to show how craps games applied on that test, will be carried out theoretical analysis by applying a variety of statistical theory. Furthermore, empirical observations will be done by applying craps test on a PRNG in order to check the test effectiveness in detecting the distribution and independency of sequences which produced by PRNG